A Systematic Review of Fatigue in Type 2 Diabetes - Bayu Febriandhika Hidayat; Tintin Sukartini; Tiyas Kusumaningrum (Jurnal Ners, 2020)
Introduction: Fatigue is often found in people with type 2 diabetes and it is known as Diabetes Fatigue Syndrome. Fatigue is a widespread clinical complaint among people with type 2 diabetes (T2DM). It has been directly related to poor self-reported health and it is likely a key barrier to the successful self-management of diabetes. The aim of this study was to identify fatigue in type 2 diabetes.Methods: The databases used to identify suitable articles were Scopus, Science Direct and PubMed limited articles published between 2012 and 2019 in English with the full text available. The search utilized the keywords of “diabetes, fatigue, diabetes fatigue syndrome, and type 2 diabetes”. Searching for the articles also used “AND”. Following the search, 7 articles met the inclusion criteria.Results: The studies were classified into 3 groups based on the causes of fatigue. The causes of fatigue involve physiological factors, psychological factors and lifestyle factors.Conclusion: Diabetes fatigue syndrome is defined as a multifactor syndrome of fatigue or easy fatigability occurring in persons with diabetes caused by a variety of lifestyle, nutritional, medical, psychological, glycemia/diabetes-related, endocrine, and iatrogenic factors.